Endoscopic Endonasal Approach to a Giant Dentigerous Cyst - Eren Yılmaz; Aytuğ Altundağ; Pelin Dülgeroğlu Karamık; Düzgün Yıldırım; Kemal Behzatoğlu (The Turkish Journal of Ear Nose and Throat)
Dentigerous cysts constitute 20% of all odontogenic cysts and are often located in the mandible and maxilla. They are often seen at young ages and in men. Patients are usually asymptomatic, and the diagnosis is established by dental radiographs in routine scans. Surgery is recommended for dentigerous cysts because ameloblastoma, intraosseous mucoepidermoid carcinoma, or intraosseous squamous cell carcinoma may develop from them. Generally the transoral route is preferred over the endoscopic route for dentigerous cysts located in the maxilla. In addition to the question of the transnasal versus oral approach to dentigerous cysts, another controversy is the removal or marsupialization of the entire cyst. In our 10-year-old male patient, a cyst that completely filled the right maxillary sinus and eroded the lateral and anterior wall of the maxillary sinus was treated with transnasal endoscopic surgery. The cyst wall and 3 permanent teeth were removed endoscopically. No post-operative complications were observed. The patient’s age and the location and size of the cyst play an important role in the choice of treatment. Furthermore, the most accurate way to choose the appropriate treatment is to make the treatment decision with a multidisciplinary approach.